Estimation of spalling properties of wall surface based on time frequency analysis of hammering sound. (December 2021) - Kitamura, Yuto; Takayama, Jun-ya
Abstract: In this report, we focused on the diagnosis of wall spalling in condominiums, etc., and tried to estimate the size and shape of spalling by analyzing the hammering sound based on the power spectrum. In particular, we confirmed that the frequency at which the power becomes maximum tends to change depending on the hammering position. In addition, by introducing a vibration model, we examined the quantitative estimation of spalling, and discussed the possibility of searching for spalling and estimating spalling shape by focusing on the change in the power of the spalling-specific frequencies and the tile-specific frequencies at each hammering position.